2013
DOI: 10.1093/jrr/rrt057
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with chordomas/chondrosarcomas during treatment with proton beam therapy

Abstract: Introduction: Health-related quality of life (HQL) parameters have never been tested in patients having chondromas/chondrosarcomas who are being treated with protons. The aim of this study was to document changes in HQL of chordoma/chondrosarcoma patients treated with proton beam radiotherapy. Treatments commenced in September 2011 at CNAO, and HQL studies were initiated in January 2012 for all patients undergoing treatment. Methods: The validated Italian translation of the EORTC QLQ-C30 version 3.0 was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
1
25
1
Order By: Relevance
“…Four studies reported HRQoL data from patients at both diagnostic and treatment phases. [39][40][41][42] Patients with sarcoma Compared with the general population, patients with sarcoma reported lower mean scores on all HRQoL scales, resulting in a lower mean global health score. 39 Compared with pretreatment scores, patients with sarcoma treated with radiotherapy and/or chemotherapy reported lower physical functioning, and more fatigue, nausea/vomiting, appetite loss, but less pain and a higher overall HRQoL score.…”
Section: At Diagnosis and Treatmentmentioning
confidence: 99%
“…Four studies reported HRQoL data from patients at both diagnostic and treatment phases. [39][40][41][42] Patients with sarcoma Compared with the general population, patients with sarcoma reported lower mean scores on all HRQoL scales, resulting in a lower mean global health score. 39 Compared with pretreatment scores, patients with sarcoma treated with radiotherapy and/or chemotherapy reported lower physical functioning, and more fatigue, nausea/vomiting, appetite loss, but less pain and a higher overall HRQoL score.…”
Section: At Diagnosis and Treatmentmentioning
confidence: 99%
“…To determine what issues should be addressed in a survey for patients with sacral tumors, we hypothesized the existence of six domains based on the current literature: mental health, physical health, pain, gastrointestinal symptoms, sexual function, and urinary incontinence [6, 7, 27, 36, 39, 41, 45]. To assess content validity, we contacted 80 patients (of whom 32 responded, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of these major surgeries on neurological, physical, psychological, social, and emotional functioning is substantial and can have a major impact on a patients’ quality of life [7, 27, 31, 36, 44]. It is important to accurately measure these outcomes in order to: (1) understand the impact of treatment on patients, (2) educate future patients, and (3) compare treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Rosenberg et al (5) reported LC rates at 5 and 10 years of 99% and 98%, respectively, and OS of 99% at 5 and 10 years when treating 200 CS with surgery then proton beam therapy; similar results have been reported by others (71) . Encouragingly, Srivastava et al (72) report that proton beam therapy does not have a significant impact on health-related quality of life parameters.…”
Section: Chemotherapy and Radiotherapymentioning
confidence: 99%